A estratégia discursiva da rotulação : léxico, argumentação e textualidade - Alves Junior, Mário Acrisio (2011)
This research aims to investigate the behavior of labels in texts belonging to genre of the jornalistic/media field, based on a social-interactional and discursive conception of language, and being guided by the widespread idea that the labelling process acts from the textual level to the level of enunciation through its multi-funcionality: it operates the organization of the textual and discoursive surface, besides being na important semantic-argumentative tool. Thus, this study focuses on recurring topics in research about labelling, as well as about other issues that should be better discussed, such as the relationship between labelling and typological sequences. Moreover, the analysis also addresses the role of enunciative modalization demonstrated by the employment of labels in texts. Labels, thus not only organize the text, but carry information about the textual contents and opinions of the speaker about certain topics, standing frequently in sentenses such comment. Throughout the text, these comments appear making the link between textual units of more complex statute which are classified by Bronckart as types of discourse.